Implementasi modul analisis konsentrasi protein terhadap hasil belajar dan respon mahasiswa pada pembelajaran biokimia II - Mellyta Uliyandari; Sumpono Sumpono; Agus Susanta (University of Bengkulu, 2019)
AbstraCT [Implementation of Module Protein Concentration Analysis on Learning Outcomes and Student Response to Biochemical Learning II]. This study aims to look at the effect of the implementation of the use of the